Foreign language education of people with hearing loss in Hungary – Sign language in Hungarian foreign language education (Training and Practice : Journal of Educational Sciences, 2018)
I have done descriptive research on sign language generally in education, and specifically in foreign language teaching. Finally, I have had the conclusion that the use of sign language in general, as well as in foreign language education, increases motivation and efficiency of hearing impaired people to learn foreign languages. In Hungary, while the right of bilingual education for hearing impaired students is well described by law (Act CXXV of 2009), in practice this is not working in the schools in Hungary. However, we see good practice of bilingual teaching methods of foreign languages in other countries of Europe.